Sensor‐Based Electromagnetic Navigation to Facilitate Implantation of Left Ventricular Leads in Cardiac Resynchronization Therapy. (29th October 2014) - DÖRING, MICHAEL; SOMMER, PHILIPP; ROLF, SASCHA; LUCAS, JOHANNES; BREITHARDT, OLE A.; HINDRICKS, GERHARD; RICHTER, SERGIO
Electromagnetic Navigation for CRT Implantation Introduction Implantation of cardiac resynchronization therapy (CRT) devices can be challenging, time consuming, and fluoroscopy intense. To facilitate placement of left ventricular (LV) leads, a novel electromagnetic navigation system (MediGuide™, St. Jude Medical, St. Paul, MN, USA) has been developed, displaying real‐time 3‐D location of sensor‐embedded delivery tools superimposed on prerecorded X‐ray cine‐loops of coronary sinus venograms. We report our experience and advanced progress in the use of this new electromagnetic tracking system to guide LV lead implantation. Methods and Results Between January 2012 and December 2013, 71 consecutive patients (69 ± 9 years, 76% male) were implanted with a CRT device using the new electromagnetic tracking system. Demographics, procedural data, and periprocedural adverse events were gathered. The impact of the operator's experience, optimized workflow, and improved software technology on procedural data were analyzed. LV lead implantation was successfully achieved in all patients without severe adverse events. Total procedure time measured 87 ± 37 minutes and the median total fluoroscopy time (skin‐to‐skin) was 4.9 (2.5–7.8) minutes with a median dose‐area‐product of 476 (260–1056) cGy*cm2. An additional comparison with conventional CRT device implantations showed a significant reduction in fluoroscopy time from 8.0 (5.8; 11.5) to 4.5 (2.8; 7.3) minutes (P = 0.016) and radiation dose from 603 (330; 969) to 338 (176; 680) cGy*cm2, respectively (P = 0.044 ). Conclusion Use of the new navigation system enables safe and successful LV lead placement with improved orientation and significantly reduced radiation exposure during CRT implantation.